Role of paraoxonase 2 (PON2) as a potential biomarker and therapeutic target in cancer treatment - Vinayak Agarwal; Matthew Cheesman; Alison Haywood; Sohil Khan; Shailendra Anoopkumar Dukie (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Paraoxonase 2 (PON2), a mitochondrial antioxidant enzyme, is widely expressed across body tissues and plays vital roles in cellular defence. Growing evidence links its dysregulation to oxidative stress and cancer progression. This narrative review aims to elucidate PON2’s enzymatic characteristics and explore its potential modulation as an innovative therapeutic avenue for combating cancer. Methods This narrative review provides a comprehensive evaluation of the roles of paraoxonase 2 in cancer, with a focus on its regulatory mechanisms and potential utility as a biomarker for targeted therapeutic interventions. A comprehensive analysis of the scientific literature from 1924 to 2024 was carried out, with studies retrieved from PubMed, Web of Science, and Scopus. Following a comprehensive screening process, 27 studies were included in the review. Results The outcomes underscore PON2's complex involvement in cancer biology, spanning tumour initiation, progression, and therapeutic resistance. The antioxidant attributes of PON2 play a critical role in helping cancer cells combat chemotherapy by allowing them to sustain oxidative stress. PON2 regulates essential features of the cancer cell lifecycle, such as invasion, migration, and proliferation. Its impact on apoptosis makes it promising as a biomarker for prognosis and diagnostics as well as a therapeutic target, especially for patients with drug-resistant cancers. Conclusion This review highlights PON2’s involvement in carcinogenesis in detail. Future research should focus on elucidating the molecular mechanisms regulating PON2 and exploring its potential as a target for the development of effective cancer therapies.